To Compare the Efficacy of Tap Water Iontophoresis Versus Aluminum Chloride Hexahydrate in the Treatment of Palmoplantar Hyperhidrosis - Asia Hafeez, Saira Niazi, Syed Hyder Raza, Ayesha Jamil, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The excessive sweating of the body beyond the physiological need is termed as hyperhidrosis. Objective: this study aimed to determine the efficacy of tap water iontophoresis and aluminium chloride for treatment of palmoplantar hyperhidrosis. Study design: It is randomized control trial based interventional study. Material and Method: This study was conducted at the Department of Dermatology, Niazi Medical and Dental College, Sargodha. The duration of the study was six month from July 2022 to December 2022. The patients diagnosed with hyperhidrosis were selected for this research. The patients included in the group 1 were treated with tape water iontophoresis (TWI). The patients included in group 2 were treated with 20% aluminium chloride hexahydrate (AC) liquid solution. This treatment was given for 4 weeks. Adherence monitoring was done by participant self-report diary and results were assessed. Results: The average value of the production of sweat was calculated. The average value of both groups indicates a difference greater than 0.05, which is non-significant. The average value was observed to be 9.76 ± 2.3 g for group no. 1, and the average percentage of production of sweat was also get lowered. While in the case of group no. 2 the reduction of the average value of sweat was 4.3 ± 1.58 and there is a reduction of percentage value up to 65.8 ± 9.87 % observed and the value for group no. 1 was significant according to the value of p. When the results of HDSS (hyperhidrosis disease severity) were compared, no significant difference was observed in the values of both groups. But at the end of the study, when the mean value of hyperhidrosis disease severity was compared in both groups, there were significant changes in group 2. Conclusion: This study was conducted to determine the treatment efficacy of tap water and aluminum chloride in controlling sweating up to normal level. It was observed that tap water along with a direct current of palmer was a much more efficient way to control the sweating level. Keywords: Hyperhidrosis, direct current, tap water iontophoresis, Aluminum Chloride hexahydrate, Hyperhidrosis severity scale (HDSS).